The Relationship Between Knowledge of Lactation Management and Breastfeeding in the Perinatology Ward of Bhakti Husada Krikilan Hospital, Banyuwangi: The Relationship Between Knowledge of Lactation Management and Breastfeeding in the Perinatology Ward of Bhakti Husada Krikilan Hospital, Banyuwangi - Sholikhah, Dwi Uswatun; Ariani, Hany Puspita; Yuanita, Dewi Ratna; Faizah, Rohmatul (Sekolah Tinggi Ilmu Kesehatan Garuda Putih, 2025)
Babies who are not breastfed are 13 times more likely to die as a child. While breastfeeding is a natural process, many mothers are unable to breastfeed their babies due to several factors, including a lack of maternal knowledge and support and promotion of formula milk. This study aims to determine the relationship between postpartum mothers' knowledge of lactation management and breastfeeding practices. The research design used was an observational analytic cross-sectional study. The study population was postpartum mothers at Bhakti Husada Krikilan General Hospital, Banyuwangi, and the sampling technique was purposive sampling, with 34 respondents. Data collection used the Breastfeeding Knowledge Questionnaire to measure knowledge and a questionnaire on exclusive breastfeeding practices. Data analysis used Spearman Rank test with a significance level of α = 0.05, resulting in a ρ value of 0.001. This indicates that ρ < α, thus, it can be concluded that the alternative hypothesis (H1) is accepted. This means there is a correlation between postpartum mothers' knowledge of lactation management and breastfeeding practices at Bhakti Husada Krikilan Hospital. Therefore, healthcare workers at the hospital are expected to consistently provide education on lactation management to further enhance the knowledge of postpartum mothers, both those with limited and good knowledge, and to ensure optimal breastfeeding practices..